KAJIAN PSIKOLOGI TOKOH UTAMA PADA NOVEL MANUSIA KALENG-KALENG KARYA KUNTA ANJANA - Nuraeni, Wini; Irma, Cintya Nurika (University of Brawijaya, 2024)
This research intend to identify and describe the id, ego, and superego of the main character in the novel Manusia Kaleng-Kaleng by Kunta Anjana. This research used descriptive qualitative method. The research technique used is data collection techniques and data analysis techniques. The data source for this research is the novel Manusia Kaleng-Kaleng by Kunta Anjana published by Guepedia Publisher, 2019. The research instrument is the human instrument. The data obtained are in the form of words, phrases, sentences and paragraphs in the novel Manusia Kaleng-Kaleng by Kunta Anjana which describes the story of the main character named Alvit who often experiences conflicts in his life from childhood to school which is always related to himself and other people surrounding. In accordance with the problem in the research, namely the analysis of the id, ego, and superego of the main character in the novel Manusia Kaleng-Kaleng by Kunta Anjana. As for the novel Manusia Kaleng-Kaleng by Kunta Anjana, it was found: (1) id a strong that make Alvit feel ashamed. (2) ego a strong that makes Alvit feel stupid, irritable, and feels bad. (3) superego a strong that makes personality Alvit a very responsible person, always enthusiastic, unyielding, and optimistic.